Endogenous lysophosphatidic acid participates in vascularisation and decidualisation at the maternal-fetal interface in the rat. The fundamental role of LPA3 receptor in decidualization and vascularization - Sordelli, Micaela Soledad (2017)
Lysophosphatidic acid (LPA) affects several female reproductive functions through G-protein-coupled receptors. LPA contributes to embryo implantation via the lysophospholipid LPA3 receptor. In the present study we investigated the participation of endogenous LPA signalling through the LPA3 receptor in vascularisation and decidualisation, two crucial events at the maternal?fetal interface. Pregnant rats were treated with diacylglycerol pyrophosphate (DGPP), a highly selective antagonist of LPA3 receptors, on Day 5 of gestation. Pregnant rats received intrauterine (i.u.) injections of single doses of DGPP (0.1 mg kg1) in a total volume of 2 mL in the left horn (treated horn) in the morning of GD5. DGPP treatment produced aberrant embryo spacing and increased embryo resorption. The LPA3 receptor antagonist decreased the cross-sectional length of the uterine and arcuate arteries and induced histological anomalies in the decidua and placentas. Marked haemorrhagic processes, infiltration of immune cells and tissue disorganisation were observed in decidual and placental tissues from sites of resorption. The mRNA expression of three vascularisation markers, namely interleukin 10 (Il10), vascular endothelial growth factor (Vegfa) and vascular endothelial growth factor receptor 1 (Vegfr1), was reduced at sites of resorption from Day 8. The results show that the disruption of endogenous LPA signalling by blocking the LPA3 receptor modified the development of uterine vessels with consequences in the formation of the decidua and placenta and in the growth of embryos.